A stochastic framework for the assessment of horizontally curved aluminium bridge decks on steel girders. (August 2022) - Shittu, Abdulhakim Adeoye; Abejide, Samuel; Olisa, Samuel Chukwuemeka; Mehmanparast, Ali; Kolios, Athanasios
Abstract: A purpose-developed structural reliability assessment (SRA) framework for the evaluation of horizontally curved aluminium alloy bridge decks on steel I-girders of centre subtended angle, θ ≤ 34.4 with precinct on the American association of state highway and transportation officials (AASHTO) load resistance factor design (LRFD) specification is presented. The finite element analysis (FEA) simulations were performed in the ABAQUS© CAE, whilst the probabilistic assessment model was developed using the first-order reliability method (FORM). Besides performing detailed design checks and a validation exercise, the developed SRA framework was used to examine the structural behaviour of the bridge assembly in the presence of stochastic design truck axle loads, structure's self-weight, among other loads, whilst varying geometric properties. The most critical structural responses chosen at salient points obtained via FEA simulation is applied in deriving the limit state function (LSF), which is then substituted into the stochastic model within the purpose-developed iterative FORM algorithm to calculate the reliability index (RI), β of the structure. It is shown that the proprietary Alumadeck TM system conforms with the LRFD specification, which stipulates that the target value of RI is 3.5 for resistance factor (RF) of 1.0 (assuming 80% composite action compression flange). The result also reveals that the RI shows a strong dependence on the composite action between the deck and the girder for RF of 1.0 full composite action (considering the failure of the bottom flange), indicating the safety index is within acceptable limits. Furthermore, it is revealed that the minimum composite action for safety is 40%, corresponding to a safety index of 1.16. Hence, it can be inferred from the foregoing that the Alumadeck TM can withstand the stochastic axle load it is subjected to considering the HL-93 load design condition and satisfies all design criteria considered from a stochastic perspective based on the AASHTO LRFD guidelines, provided the minimum stiffner thickness t stiffner of 7 m m is adopted (based on the FEA simulation results). A case study conducted herein established that the structural configuration selected (i.e. depth at 2.4 m, flange thicknesses at 21 m m, flange width at 50 c m and web thickness at 16 m m ) demonstrates the structural safety and durability of the bridge system coupled using the Alumadeck TM .